IMPLEMENTASI TEKNOLOGI DALAM DESAIN PEMBELAJARAN INTERAKTIF UNTUK MEGOPTIMALKAN KEMAMPUAN KOGNITIF ANAK - Tiara Lisa Br Tarigan; Nurdianti; Nur Intan; Mayzura; Khairunnisa Mifta Ababil (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
This research explores the implementation of technology in interactive learning design to enhance children's cognitive skills. The problem revolves around the lack of engagement and effectiveness in traditional learning methods to facilitate children's cognitive development. The aim is to investigate the extent to which technology usage can improve engagement and cognitive learning outcomes. The research methodology involves the development and implementation of technology-based learning applications specifically designed to reinforce children's cognitive skills. Data were collected through participatory observation, interviews, and cognitive tests. The results indicate that interactive learning design with technology is effective in enhancing engagement and cognitive learning outcomes for children. In conclusion, integrating technology into learning can be an effective approach to strengthening children's cognitive skills, providing more engaging and enriching learning experiences.